A method for quick and efficient identification of cichlid species by high resolution DNA melting analysis of minibarcodes - Tadmor-Levi, Roni; Cummings, David; Borovski, Tomer; Shapira, Rachel; Marcos-Hadad, Evgeniya; David, Lior (Frontiers in Ecology and Evolution, 2022)
Freshwater bodies are key in supporting aquatic and terrestrial life. Ecological balance of freshwater habitats is very vulnerable, hence, often significantly disrupted by climatic changes and anthropogenic acts. In Israel, due to its relatively arid climate, many freshwater resources have been disrupted and still are under great pressure. The Sea of Galilee is the largest surface freshwater body in the Middle East and a habitat to unique populations of several fishes, including six cichlid species. Studies on the ecology of these fish and their conservation require effective monitoring tools. In this study, a simple and efficient molecular method was developed to identify the species of these lake cichlids using high resolution melting analysis of mini DNA barcodes. The species of an individual sample can be identified by a single tube PCR reaction. This assay successfully identified sequence differences both among and within species. Here, this method identified the species for 279 small cichlid fry that could not be morphologically identified, allowing to estimate relative species abundance and map their distribution in time and location. The results are key to understand not only the ecology of young stages but also their recruitment potential to adult fish populations and their sustainability. This method can be readily implemented in further ecological studies and surveys related to these species, in the lake and its surroundings, as a tool to enhance understanding and protection of these species.